(untitled) (Bangladesh Journal of Pharmacology, 2016)
P-glycoprotein (P-gp) is a membrane transporter responsible for the active efflux from the cell. Inhibition of the activity may lead to clinically significant drug-drug interactions. This study was performed to investigate the effects of atorvastatin and ezetimibe on the function and expression of P-gp. The in vitro rhodamine-123 (Rho123) efflux assay and Western blot in Caco-2 cells, and the in situ rat single-pass intestinal permeability model followed by high performance liquid chromatography were developed. Rho123 intracellular accumulation in 100 µM of atorvastatin- and ezetimibe-treated cells was significantly higher than that in control cells (p<0.05). P-gp expression was decreased by 100 µM atorvastatin and ezetimibe. Intestinal effective permeability of digoxin in the presence of atorvastatin (3 and 100 µM), ezetimibe (10 and 100 µM) was significantly increased (p<0.05). Both drugs inhibited P-gp activity in vitro and in situ. Atorvastatin and ezetimibe down-regulated the expression of P-gp in vitro. Video Clip of Methodology: Single-pass intestinal permeability: 17 min 26 sec Full Screen Alternative